2014
DOI: 10.1037/a0038010
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of pitch contour, tonality, rhythm, and meter to melodic similarity.

Abstract: The identity of a given melody resides in its sequence of pitches and durations, both of which exhibit surface details as well as structural properties. For the purposes of this research, pitch contour (pattern of ups and downs) served as pitch surface information, and tonality (musical key) as pitch structure; in the temporal dimension, surface information was the ordinal duration ratios of adjacent notes (rhythm), and metre (beat, or pulse) comprised the structure.Manipulating factorially the preservation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 123 publications
(206 reference statements)
2
29
0
6
Order By: Relevance
“…In Experiment 1, using a standard probe sequence recognition paradigm, many participants reported using a visual strategy, favoring global matching procedures based on the comparison of contour-based relational shape patterns of the target and probe musical sequences [72] rather than storage of separated item representations and item-serial position associations. Previous experiments in musical cognition showed that the salience of a dimension such as pitch or temporal structure can prioritize the processing of one of them at the expense of the other [7678]. Providing full melodic context at encoding and recognition, as we did in Experiment 1, could therefore have prioritized the processing of global contour shape information, at the expense of detailed, item-based pitch processing.…”
Section: Discussionmentioning
confidence: 73%
“…In Experiment 1, using a standard probe sequence recognition paradigm, many participants reported using a visual strategy, favoring global matching procedures based on the comparison of contour-based relational shape patterns of the target and probe musical sequences [72] rather than storage of separated item representations and item-serial position associations. Previous experiments in musical cognition showed that the salience of a dimension such as pitch or temporal structure can prioritize the processing of one of them at the expense of the other [7678]. Providing full melodic context at encoding and recognition, as we did in Experiment 1, could therefore have prioritized the processing of global contour shape information, at the expense of detailed, item-based pitch processing.…”
Section: Discussionmentioning
confidence: 73%
“…Instead of detecting differences between melodies, the participant's task is to evaluate the similarity of these melodies (e.g. Eerola & Bregman, 2007;Müllensiefen & Frieler, 2007;Prince, 2014). However, whether the task is to evaluate melodic similarity or to detect melodic differences seems to make little difference to response patterns (Bartlett & Dowling, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…We note that some preliminary support for the separation of brain activities during rhythm-related movement from brain activities during non-rhythm-related movement was reported (Brown et al, 2005; Phillips-Silver, 2009). Some experiments demonstrated that the perception of rhythm may influence the perception of melody (Prince, 2014). The consistency of the somatic of musicality of dancers, as well as the reasons for it, needs further investigation.…”
Section: Discussionmentioning
confidence: 99%